PENINGKATAN KEMAMPUAN MENULIS PANTUN SISWA KELAS IV SD NEGERI 066044 KECAMATAN MEDAN HELVETIA KOTA MEDAN DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING THINK PAIR SHARE - AZMI YULIANA (JURNAL ILMIAH SIMANTEK, 2020)
This research aims to improve the student’s ability for completing hiatus paragraphs and student activities. Research isclassroom action research with the number 37 students. The instruments used is the test of hiatus paragraph, observation ofstudent activity. Analysis of the data to see an increase the ability of narrative writing, and student activity have Ms. ExcelProgram. The results showed that peer tutoring learning model can improve the ability for completing the hiatus paragraphs.Cycle I obtained an average value of 71.38. The number of students who scored 65 (category enough) were 29 studentsfrom 37 students who take the test, or the level of mastery learning students is 78.38%. Cycle II obtained average value80.71. The number of students who earn a minimum category "sufficient" (minimum value of 65.0) were 31 students of the37 students who take the test, or the level of students' ability to complete the hiatus paragraph is 83.78%. Of the 16indicators of student activity in the first cycle, there are 4 (four) or indicators (25%) met the indicators of success measures.But on the second cycle, all indicators have met the indicators of success. The model of learning peer tutor may be analternative for teachers in presenting lessons on the material of hiatus paragraph completing.